KBS (KARTU BERBAHASA) SEBAGAI SARANA MENINGKATKAN SIKAP BERBAHASA PESERTA DIDIK TK FIP UMJ - Lutfi Syauki Faznur (Jurnal Akrab Juara, 2018)
The purpose of this research is to produce some of the learning media language card in introducing the rule of Indonesian Language for FIP UMJ Kindergarten. The kind of this research is Research and Development which is using a research procedure from Borg and Gall. The research using 7 of 10 Borg and Gall steps, i.e.: early stage of collecting the data, planning stage, early stage of product designing, product experiment stage, product revision from the media and material expert stage, the field test stage, and conlusion of the product stage. The subject of this research is the students of FIP UMJ Kindergarten. The method of Data Analysis is using decriptive qualitative approach and descriptive quantitative percentage.The result of research and development for language cards has been categorized with 81% level of eligibility. The level of egibility from media aspect is 82%, at the same time the level of egibility from material expert is 91%. The whole result of this language card has been declared feasible to be used for Indonesian language learning media in determine young learner speaking attitude after passing the experiment phase with the very good feasibility category.